De Novo Inflammatory Bowel Disease Rarely Occurs During Posttransplant Immunosuppression. Issue 6 (14th June 2021) - Fang, Jiayun M; Lamps, Laura; Yeboah-Korang, Amoah; Cheng, Jerome; Westerhoff, Maria
Abstract: Objectives: De novo chronic idiopathic inflammatory bowel disease (CIIBD) is reported to occur at higher rates in posttransplant patients than that of the general population. The previous reports, however, included patients with primary sclerosing cholangitis (PSC), a known association with CIIBD. Hence, we investigated how often posttransplant de novo CIIBD occurs in the absence of PSC. Methods: We identified 185 posttransplant adults without a history of PSC or CIIBD, who had undergone colonoscopy between July 2013 and June 2020. Biopsies were reviewed and clinical data were gathered. Results: CIIBD-like colitis accounted for 1.1% (2/185) of our cohort. The 2 affected patients were already taking multiple immunosuppressive therapies. They were initially placed on standard CIIBD maintenance therapy, but then required escalation therapy. One patient had persistent active colitis despite escalation therapy, while the other subsequently had resolution of symptoms and developed quiescent disease. Conclusions: The incidence of CIIBD-like colitis in our study population was lower than what has been previously described. Both patients had a poor response to standard CIIBD therapy, raising the question whether their diagnosis is truly de novo CIIBD or another immunologic process.